Electronic features of cotton fabric e-textiles prepared with aqueous carbon nanofiber inks - Paleo, Antonio J. (2023)
Cotton woven fabrics functionalized with aqueous inks made with carbon nanofibers (CNFs) and anionic surfactant are prepared via dip-coating followed by heat treatment, and their electronic properties are discussed. The e-textiles prepared with the inks made with the highest amount of CNFs (6.4 mg mL−1 ) show electrical conductivities (σ) of ∼35 S m−1 and a negative Seebeck (S) of −6 μV K−1 at 30 °C, which means that their majority carriers are electrons. The σ(T) of the e-textiles from 30 to 100 °C shows a negative temperature effect, interpreted as a thermally activated hopping mechanism across a random network of potential wells by means of the 3D variable range hopping (VRH) model. Likewise, their S(T) from 30 to 100 °C shows a negative temperature effect, conveniently depicted by the same model proposed for describing the negative Seebeck of doped multiwall carbon nanotube mats. From this model, it is deduced that the cause of the negative Seebeck in the e-textiles may arise from the contribution of the impurities found in the as-received CNFs, which cause sharply varying and localized states at approximately 0.085 eV above their Fermi energy level (EF). Moreover, the possibility of a slight n-doping from the cellulose fibers of the fabrics and the residuals of the anionic surfactant onto the most external CNF graphitic shells present in the e-textiles is also discussed with the help of the σ(T) and S(T) analysis.